Efektivitas Penyuluhan Anti-Bullying dan Kenakalan Remaja Berbasis Hak Asasi Manusia terhadap Pemahaman Siswa SMPN 50 Bandung - Rafael Ahmad Eryasafli; Wardatul Azizah; Siti Ulfah Awaliyah; Muhammad Faiz Zakwan (Yayasan Al-Afif, 2025)
This study aims to examine how a Human Rights–based Anti-Bullying outreach program can improve students’ understanding of bullying and juvenile misconduct at SMPN 50 Bandung. The activity involved delivering materials and conducting focus group discussions with 33 student representatives from all classes. The outreach covered various forms of bullying commonly found at school, with verbal bullying identified as the most frequent. The discussion also included types of juvenile misconduct such as skipping class, speaking disrespectfully, fighting and other behaviors that disturb the learning environment. The results show that students gained a clearer understanding of the impact of their actions on their peers and the school environment. Through the FGD sessions, students were able to analyze real cases and connect them with human rights principles, demonstrating that the program not only increased knowledge but also encouraged changes in students’ perspectives and attitudes.